Study protocol: The efficacy of mushroom to prevent cognitive decline in at-risk middle-aged adults and young-olds living in the community - Shan, Jiatong; Cao, Luwen; Guo, Jiuyu; Lim, Kai Xuan; Li, Na; Chao, Yinxia; Xie, Yizhen; Chen, Jian; Ma, Wei; Lim, Su Lin; Cheah, Irwin Kee-Mun; Gandhi, Mihir; et al. (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive function declines with increasing age and maintaining high cognitive functioning especially at late life remains a challenging question to be addressed. Emerging evidence in the role of mushroom in promoting cognition has been produced from limited observational studies but there is a lack of definitive evidence on both longitudinal relationships from prospective cohort studies and clinical efficacy from clinical trials.ObjectivesTo explore the definitive evidence of mushroom on cognitive functions among at-risk middle-aged and young-olds.DesignThe first study is a 10-year cognitive assessment follow-up on an existing cohort, the Diet and Healthy Aging (DaHA), which recruited over 1,000 older adults from the year 2010 to the year 2016. The second is a carefully designed randomized controlled trial (RCT) to assess the role of mushrooms in promoting cognitive functioning among around 600 middle-aged adults and young-olds.ParticipantsParticipants were selected based on specific inclusion criteria, such as being community-living adults aged 45–74 years with a family history of dementia, APOE ε4 allele, or subjective cognitive decline, while consuming mushrooms no more than once a week and having no dementia, along with the exclusion of individuals with neurological or psychiatric disorders and significant sensory or motor impairments.InterventionParticipants in the intervention group will consume Pleurotus citrinopileatus mushroom powder daily for 24 months, with compliance monitored using electronic diary apps. The powder contains 7.0 mg/g of ergothioneine (dry weight).MeasurementsCognitive function including Mini Mental State Examination, Rey Auditory Verbal Learning Test, Symbol Digit Modality test, Clinical Dementia Rating etc. along with mental health and biological markers will be measured at baseline, 1 year, and 2 years after baseline.